2018
DOI: 10.1007/s40572-018-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Air Pollution on the Brain: a Review of Studies Interfacing Environmental Epidemiology and Neuroimaging

Abstract: Purpose of ReviewAn emerging body of evidence has raised concern regarding the potentially harmful effects of inhaled pollutants on the central nervous system during the last decade. In the general population, traffic-related air pollution (TRAP) exposure has been associated with adverse effects on cognitive, behavior, and psychomotor development in children, and with cognitive decline and higher risk of dementia in the elderly. Recently, studies have interfaced environmental epidemiology with magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 75 publications
2
97
0
1
Order By: Relevance
“…In addition to possible associations between exposure to air pollution and reduced volume in specific brain regions, such as smaller hippocampal volume [9], exposure to air pollution might also be associated with reduced overall gray-matter and white-matter volume. In this regard, exposure to air pollution has been associated with smaller white-matter volume in children and adult women [10][11][12], with reduced gray-matter and white-matter volume in older adults [11], and with reduced total cerebral volume in older adults [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to possible associations between exposure to air pollution and reduced volume in specific brain regions, such as smaller hippocampal volume [9], exposure to air pollution might also be associated with reduced overall gray-matter and white-matter volume. In this regard, exposure to air pollution has been associated with smaller white-matter volume in children and adult women [10][11][12], with reduced gray-matter and white-matter volume in older adults [11], and with reduced total cerebral volume in older adults [13].…”
Section: Introductionmentioning
confidence: 99%
“…Children are particularly susceptible to air pollutants, and pre-and/or postnatal exposure may negatively affect their CNS [35]. Recently, several investigation studies have integrated magnetic resonance imaging of the brain with epidemiology, showing that long-term exposure to air pollution might have adverse impacts on the human brain [36]. A recent study has shown that prenatal exposure to PM 2.5 may be associated with a corpus callosum (CC) volume decrease in children.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging methods allow a more precise and accelerated diagnosis of numerous diseases related to the exposition of air pollutants; investigators from different parts of the world are using imaging methods such as plain radiography [42], ultrasonography (US), echocardiography [9], computed tomography (CT) [43] and magnetic resonance imaging (MRI) [7], to help us understand environmental disease pathophysiology and evolution ( Table 2).…”
Section: Imaging Methods Used In the Assessment Of Environmental Disementioning
confidence: 99%
“…Air pollution is a combination of diverse gases and particles; pollutants that represent a significant public health problem involve particulate matter (PM), a mixture of elemental and organic carbon, polycyclic aromatic (PAH) and metals hydrocarbons, ozone (O 3 ), carbon monoxide (CO), lead, sulfur dioxide (SO 2 ) and nitrogen dioxide (NO 2 ) [7].. They are derived from the various natural and anthropogenic origin.…”
Section: Chemical Substances Linked To Environmental Diseasesmentioning
confidence: 99%
See 1 more Smart Citation